Characterization of patients with longstanding idiopathic REM sleep behavior disorder. (18th July 2017) - Iranzo, Alex; Stefani, Ambra; Serradell, Monica; Martí, Maria Jose; Lomeña, Francisco; Mahlknecht, Philipp; Stockner, Heike; Gaig, Carles; Fernández-Arcos, Ana; Poewe, Werner; Tolosa, Eduard; Högl, Birgit; et al.
Abstract : Objective: To evaluate the presence of prodromal markers of Parkinson disease (PD) in patients with longstanding idiopathic REM sleep behavior disorder (IRBD), a small subgroup of individuals with IRBD with long-term follow-up thought not to be at risk of developing PD. Methods: Demographic, clinical, and neuroimaging markers of PD were evaluated in 20 patients with polysomnographic-confirmed longstanding IRBD and in 32 matched controls. Results: Patients were 16 men and 4 women with mean age of 72.9 ± 8.6 years and mean follow-up from IRBD diagnosis of 12.1 ± 2.6 years. Patients more often had objective smell loss (35% vs 3.4%, p = 0.003), constipation (50% vs 15.6%, p = 0.008), and mild parkinsonian signs (45% vs 18.8%, p = 0.042) than controls. Unified Parkinson's Disease Rating Scale motor score was higher in patients than in controls (5.6 ± 3.5 vs 2.0 ± 2.1, p < 0.0001). Dopamine transporter imaging showed decreased striatal uptake in 82.4% of the patients and transcranial sonography found substantia nigra hyperechogenicity in 35.3%. α-Synuclein aggregates were found in 3 of 6 patients who underwent colon or submandibular gland biopsies. All 20 patients showed clinical, neuroimaging, or histologic markers of PD. Probability of prodromal PD (according to recent Movement Disorders Society research criteria) was higher in patients than in controls (<0.0001), and 45% of patients surpassed 80% probability. Conclusions: Prodromal PD markers are common in individuals with longstanding IRBD, suggesting that they are affected by an underlying neurodegenerative process. This observation may be useful for the design of disease-modifying trials to prevent PD onset in IRBD.